The dual role of platelet‐innate immune cell interactions in thrombo‐inflammation - Rayes, Julie (Res Pract Thromb Haemost, 2019)
Beyond their role in hemostasis and thrombosis, platelets are increasingly recognized as key regulators of the inflammatory response under sterile and infectious conditions. Both platelet receptors and secretion are critical for these functions and contribute to their interaction with the endothelium and innate immune system. Platelet‐leukocyte interactions are increased in thrombo‐inflammatory diseases and are sensitive biomarkers for platelet activation and targets for the development of new therapies. The crosstalk between platelets and innate immune cells promotes thrombosis, inflammation, and tissue damage. However, recent studies have shown that these interactions also regulate the resolution of inflammation, tissue repair, and wound healing. Many of the platelet and leukocyte receptors involved in these bidirectional interactions are not selective for a subset of immune cells. However, specific heterotypic interactions occur in different vascular beds and inflammatory conditions, raising the possibility of disease‐ and organ‐specific pathways of intervention. In this review, we highlight and discuss prominent and emerging interrelationships between platelets and innate immune cells and their dual role in the regulation of the inflammatory response in sterile and infectious thrombo‐inflammatory diseases. A better understanding of the functional relevance of these interactions in different vascular beds may provide opportunities for successful therapeutic interventions to regulate the development, progression, and chronicity of various pathological processes.